Treatment of Adults with Major Depressive Disorder with Peripartum Onset Using Cognitive Behavior Therapy - Triyanti, Marisa Shinta; Surjaningrum, Endang R. (Psikoborneo: Jurnal Ilmiah Psikologi, 2025)
This study aims to determine the experiences of clients with major depressive disorders with peripartum onset and the application of cognitive behavior therapy in intervention. The client in this study was a 24-year-old mother who experienced symptoms during pregnancy and postpartum and even had the desire to harm herself and her child. A series of psychological examinations are carried out such as observation, interviews, graphics, BDI and postpartum depression scale to determine the client's condition. The intervention carried out with Cognitive Behavior Therapy consisted of 6 sessions. The results of this examination and intervention found that unpreparedness to have children, sexual harassment/coercion, lack of family support and late examination and treatment influenced symptoms which resulted in the emergence of cognitive distortions (unsuccessful becoming a mother, blaming oneself) and had an impact on daily behavior as well as thoughts and trying to hurt yourself and your child. Clients changed cognitive distortions and applied adaptive cognitive in daily behavior to reduce the appearance of symptoms of major depressive disorder with peripartum onset. Penelitian ini bertujuan untuk mengetahui pengalaman klien dengan major depressive disorder with peripartum onset dan penerapan cognitive behavior therapy pada intervensi. Klien dalam penelitian ini adalah seorang perempuan berusia 24 tahun yang mengalami gejala ketika mengandung hingga pasca melahirkan bahkan memiliki keinginan untuk menyakiti diri dan anak. Serangkaian pemeriksaan psikologis dilakukan seperti observasi, wawancara, grafis, BDI dan skala depresi postpartum untuk mengetahui kondisi klien. Intervensi dilakukan dengan Cognitive Behavior Therapy terdiri dari 6 sesi. Hasil dari pemeriksaan dan intervensi ini menemukan bahwa ketidaksiapan dalam memiliki anak, pelecehan/pemaksaan seksual, kurangnya dukungan keluarga dan pemeriksaan serta penanganan yang terlambat mempengaruhi gejala yang berdampak pada munculnya distorsi kognitif (tidak berhasil menjadi seorang Ibu, menyalahkan diri) dan berdampak pada perilaku sehari-hari serta pikiran dan mencoba untuk melukai diri dan anak. Klien merubah distorsi kognitif serta menerapkan kognitif adaptif dalam perilaku sehari-hari sehingga mengurangi munculnya gejala major depressive disorder with peripartum onset.